Pengaruh Modifikasi Media Penyulingan Dan Waktu Penampung Nira Bunga Lontar Jantan (Borassus Flabellifer L.) Terhadap Kualitas Produk Sopi Timor (Tua nakaf). - Yakobus Pffeferius Edvent Saba Agu; Syprianus Ceunfin; Yohanes Neno (Savana Cendana, 2023)
Sopi is an alcoholic drink distilled from Nira Lontar. For the indigenous people, dawan Sopi is a traditional drink, a cultural symbol and a tie for friendship between family members, for example as a traditional conversation starter and or media for solving problems. The problem that is happening in today's society is that people still tend to apply the conventional distillation process or their ancestral heritage, which requires a relatively longer time to produce the best quality sopi. Shok is a medium used from bamboo which is used for sopi distillation. The formulation of the problems in this study are i) How does the modification of the distillation medium (high shock) affect the quality of Timor sopi products, ii) How is the quality of Timor sopi products based on the length of storage time for sap of 24 hours and 12 hours of palm flower. This study aims to determine the effect of modified distillation media on the quality of Timor sopi products. To find out the quality of Sopi Timor products based on the length of time for palm sap to be stored. This research was carried out in Lanaus Village from September to October 2020. The palm sap used as research raw material was tapped from male lontar trees that grow around plantations and community forests in Lanaus Village, Insana Tengah District, TTU-NTT Regency. This study used a completely randomized design (CRD), which consisted of 2 factors. The results showed that there was no interaction between high shock treatment and sap storage time on parameters of sap alcohol content, sap acidity, sap soluble solids, sopi alcohol content, sopi acidity degree, and sopi soluble solids. The high shock treatment greatly affected the sopi alcohol content, this was indicated by the value of the sopi alcohol content at 12 hours of distillation at 3 meters high shock treatment where the yield reached an alcohol content of 48.33%. The duration of the sap storage has a significant effect on the quality of sopi, this is exemplified by the storage time of 12 hours in the morning giving the highest value of sap alcohol content and degree of acidity, while the soluble solids of the sap treatment of 12 hours in the afternoon give the highest soluble solids value. However, for the parameters of sopi alcohol content, degree of acidity of sopi and dissolved solids of sopi, the best holding time is the treatment time of 12 hours afternoon (shock height 3 meters). for 12 hours afternoon and with a shock height of 3 meters.